Pertanggungjawaban Perusahaan Asuransi PT. Jasa Raharja (Persero) Kantor Perwakilan Padangsidimpuan Terhadap Korban dalam Kecelakaan Lalu Lintas Berbasis Perlindungan Hukum - Yunita Yunita; M. Citra Ramadhan; Isnaini Isnaini (Mahesa Research Center, 2023)
This study aims to analyze the role, responsibilities, implementation, and accountability of PT. Jasa Raharja (Persero) Kantor Perwakilan Padang Sidempuan, an insurance company, towards victims of traffic accidents based on legal protection. The research utilized an empirical legal research method with a descriptive analytical approach. Data were obtained through literature review and qualitative analysis of field research. The findings indicate that PT. Jasa Raharja (Persero) has a role in collecting mandatory contributions and donations from transportation owners/operators and public transportation passengers. The company is responsible for providing compensation to traffic accident victims as regulated by legislation. The implementation of responsibilities aligns with the legal regulations. However, challenges arise regarding the requirements and processing time for filing insurance claims for traffic accidents. The accountability towards traffic accident victims based on legal protection is insufficient due to public unawareness of compensation provisions and procedural requirements for submitting compensation claims. Consequently, the legal protection for traffic accident victims and the community remains unrealized